Family practice guidelines - Cash, Jill C. (New York, NY : Springer Publishing, 2024)
"We are excited to collaborate on this new sixth edition of Family Practice Guidelines. The guidelines have been written and updated by experienced nurse practitioners. This valuable resource is designed to assist nurse practitioners in organizing and using the content in a quick-reference format"--
Revised edition of: Family practice guidelines / Jill C Cash, Cheryl A Glass, Jenny Mullen, editors. Fifth edition. [2020]
Includes bibliographical references and index
Keywords: Family nursing -- Handbooks, manuals, etc.sh 88002062; Handbooks and manuals.fst01423877.http://id.worldcat.org//1423877